2019
DOI: 10.1002/smll.201901718
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of Nanoporous MoS2/VS2 Heteroarchitecture for Ultrahigh Performance Ammonia Sensors

Abstract: 2D transition metal dichalcogenides (TMDs) have received widespread interest by virtue of their excellent electrical, optical, and electrochemical characteristics. Recent studies on TMDs have revealed their versatile utilization as electrocatalysts, supercapacitors, battery materials, and sensors, etc. In this study, MoS2 nanosheets are successfully assembled on the porous VS2 (P‐VS2) scaffold to form a MoS2/VS2 heterostructure. Their gas‐sensing features, such as sensitivity and selectivity, are investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(62 citation statements)
references
References 69 publications
0
62
0
Order By: Relevance
“…Finally, in addition to the applications mentioned in Section 4, more applications need to be explored based on the intriguing coupling between metals and semiconductors in MSHSs. For example, some pioneering studies have shown the suitability of 2D material-based MSHSs in the sensing of gases, [224][225] organics, [226] and DNA. [227] In addition, the ultrafast excitonic behavior in MSHSs could broaden the applications of 2D materials in optoelectronic devices, [208] and the unique spintronic states in Fe3GeTe2-based MSHSs will be used in future magnetic storage applications.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, in addition to the applications mentioned in Section 4, more applications need to be explored based on the intriguing coupling between metals and semiconductors in MSHSs. For example, some pioneering studies have shown the suitability of 2D material-based MSHSs in the sensing of gases, [224][225] organics, [226] and DNA. [227] In addition, the ultrafast excitonic behavior in MSHSs could broaden the applications of 2D materials in optoelectronic devices, [208] and the unique spintronic states in Fe3GeTe2-based MSHSs will be used in future magnetic storage applications.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al 191 VS 2 exhibits a high adsorption uptake of Df ¼ 344.5 Hz toward 5 ppm NH 3 , which is much better than that of previously reported QCM NH 3 sensors. 193 Other p-n heterojunction gas sensors, for instance, 2D WS 2 NSs decorated with TiO 2 QDs, were proved to have a high response to NH 3 gas at room temperature. 194 Xu et al 117 and Leonardi et al 195 203 The recommended concentration of NO for healthy people is below 25 ppb; when it is higher than 50 ppb, it is perhaps a sign of airway inammation.…”
Section: Inorganic Gasesmentioning
confidence: 99%
“…2D materials, such as graphene and transition metal dichalcogenides (TMDCs), have attracted incredible interest because of their extraordinary properties that make them promising candidates for next generation electronic and optoelectronic applications. [ 1–10 ] In contrast to graphene, TMDCs are semiconducting materials with layer‐dependent bandgap in the range of 1−2 eV, [ 11,12 ] exhibiting rich novel fundamental physical properties and promising applications in electronics and optoelectronics. [ 13–16 ] In spite of the attractive photoresponse performances, most of photodetectors based on TMDCs only show photoresponse in visible range, [ 17–19 ] which seriously hinder their real applications.…”
Section: Introductionmentioning
confidence: 99%